Mechanisms of Cisplatin-Induced Acute Kidney Injury: Pathological Mechanisms, Pharmacological Interventions, and Genetic Mitigations - McSweeney, Kristen Renee (Cancers (Basel), 2021)
SIMPLE SUMMARY: Nephrotoxicity is the dose-limiting factor of cisplatin treatment. Nephrotoxicity is characterized by reduced kidney function. Although an often-reversible condition, effects are notably seen years after treatment with cisplatin has ceased. It has an extensive pathophysiological map. The purpose of this article is to consolidate cisplatin-induced acute kidney injury literature and present it in one collective paper. It explores each individual mechanism linked to the disease, the pharmacological options that have been tested to target each of them, and the results obtained by each study. The paper also describes genetic modification studies and their effectiveness in preventing disease development. ABSTRACT: Administration of the chemotherapeutic agent cisplatin leads to acute kidney injury (AKI). Cisplatin-induced AKI (CIAKI) has a complex pathophysiological map, which has been linked to cellular uptake and efflux, apoptosis, vascular injury, oxidative and endoplasmic reticulum stress, and inflammation. Despite research efforts, pharmaceutical interventions, and clinical trials spanning over several decades, a consistent and stable pharmacological treatment option to reduce AKI in patients receiving cisplatin remains unavailable. This has been predominately linked to the incomplete understanding of CIAKI pathophysiology and molecular mechanisms involved. Herein, we detail the extensively known pathophysiology of cisplatin-induced nephrotoxicity that manifests and the variety of pharmacological and genetic alteration studies that target them.